POTENSI HAZARD DI LABORATORIUM GIGI PADA PEMBUATAN PERANTI ORTODONTI LEPAS DAN REKOMENDASI PENGENDALIANNYA - Sinkka Adekia Wulandandari; Winda kusumawardani; Sri Redjeki Indiani; Sianiwati Goenharto; Anisa Nur Halimah; Narta Nikita Indiani; Widya Ulfa (Universitas Lambung Mangkurat, 2025)
ABSTRACT Background: Dental laboratories, as facilities for the fabrication of removable orthodontic appliances, present various occupational hazards, including mechanical, chemical, physical, and biological risks that may endanger dental technicians. The fabrication process involves the use of diverse materials and equipment, such as acrylic resin, metal wires, alcohol burners, and high-speed cutting machines, all of which may cause injuries or work-related health problems. Therefore, hazard identification and control measures are essential to minimize the risk of occupational accidents and adverse health effects. Objective: This study aims to identify potential hazards that may occur during the fabrication of removable orthodontic appliances in dental laboratories and to provide effective and practical control recommendations to ensure a safe and productive working environment. Case: In dental laboratory practice, work-related complaints and accidents frequently occur, including cuts from sharp instruments, skin irritation due to exposure to acrylic monomer, respiratory problems caused by acrylic dust, and discomfort resulting from noise and heat generated by machinery. In addition, non-ergonomic working postures contribute to back pain and fatigue, while biological contamination risks may arise from dental impressions or patient models that are not adequately sterilized. The development of hazard control posters can help reduce these occupational risks. Conclusion: Potential hazards in dental laboratories include mechanical, chemical, physical, and biological hazards, each of which may compromise technician safety. Specific control measures tailored to each type of hazard are necessary to prevent occupational accidents and to maintain a safe working environment.Keywords : dental laboratory, hazard, removable orthodontic appliances ABSTRAK Latar Belakang: Laboratorium gigi sebagai tempat untuk pembuatan peranti ortodonti lepas memiliki potensi bahaya seperti bahaya mekanis, kimia, fisik, dan biologi yang dapat menimbulkan risiko bahaya bagi teknisi gigi. Proses pembuatan peranti ortodonti ini melibatkan berbagai bahan dan peralatan, seperti resin akrilik, kawat logam, spiritus, serta mesin pemotong berkecepatan tinggi, yang semuanya berpotensi menimbulkan cedera maupun gangguan kesehatan kerja. Oleh karena itu, identifikasi bahaya serta upaya pengendalian menjadi langkah penting untuk meminimalkan risiko kecelakaan dan dampak negatif terhadap kesehatan pekerja. Tujuan: Penelitian ini bertujuan untuk mengidentifikasi potensi bahaya yang mungkin terjadi selama proses pembuatan perant ortodonti lepas di laboratorium gigi, serta memberikan rekomendasi pengendalian yang efektif dan aplikatif agar lingkungan kerja tetap aman dan produktif. Kasus: Dalam praktik di laboratorium gigi, sering terjadi keluhan dan kecelakaan kerja seperti luka gores akibat alat tajam, iritasi kulit karena paparan monomer akrilik, gangguan pernapasan akibat debu akrilik, serta rasa tidak nyaman karena kebisingan dan panas dari mesin. Selain itu, posisi kerja yang tidak ergonomis menyebabkan nyeri punggung dan kelelahan, sementara risiko kontaminasi biologis dapat muncul dari bahan cetak atau model pasien yang belum disterilkan dengan baik, pembuatan poster yang berisi tentang pengendalian bahaya dapat meminimalkan terjadinya risiko tersebut. Kesimpulan: Potensi bahaya di laboratorium gigi meliputi bahaya mekanis, kimia, fisik, dan biologi yang masing-masing dapat mengancam keselamatan teknisi. Diperlukan pengendalian spesifik sesuai jenis bahaya untuk mencegah kecelakaan kerja dan menjaga lingkungan kerja tetap aman. Kata kunci : hazard, laboratorium gigi, peranti ortodonti lepas